2020
DOI: 10.21203/rs.3.rs-38780/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short- and long-term outcomes after colonic self-expandable metal stent placement for malignant large-bowel obstruction as a bridge to surgery focus on the feasibility of the laparoscopic approach: a retrospective, single center study

Abstract: Purpose Malignant large-bowel obstruction (MLBO) is a highly urgent condition in colorectal cancer with high complication rates. Self-expandable metal stent (SEMS) placement in MLBO is a new decompression treatment in Japan. Preoperative stent placement (bridge to surgery: BTS) avoids emergency surgery, but oncological influences of stent placement and post-BTS surgical approach remain unclear. We examined short- and long-term results of surgery for MLBO after SEMS placement in our hospital.Methods We retrosp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The technical‐ and patient‐related risk factors for colonic stenting have been identified in several Japanese studies in the last 3 years 12–17 . Regarding surgical outcomes, the advantages and disadvantages of colonic stenting for bridging for surgery were compared with those for emergency surgery and the trans‐anal decompression tube in Japanese studies and were found to be controversial 18–22 . Several studies that focused on the clinical safety and effectiveness of the self‐expandable colonic stent have been conducted in the last 3 years in Japan, most of which were limited to advanced colon cancer patients who were bridged before surgical curative therapy 1–3,5–11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical‐ and patient‐related risk factors for colonic stenting have been identified in several Japanese studies in the last 3 years 12–17 . Regarding surgical outcomes, the advantages and disadvantages of colonic stenting for bridging for surgery were compared with those for emergency surgery and the trans‐anal decompression tube in Japanese studies and were found to be controversial 18–22 . Several studies that focused on the clinical safety and effectiveness of the self‐expandable colonic stent have been conducted in the last 3 years in Japan, most of which were limited to advanced colon cancer patients who were bridged before surgical curative therapy 1–3,5–11 .…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Regarding surgical outcomes, the advantages and disadvantages of colonic stenting for bridging for surgery were compared with those for emergency surgery and the trans-anal decompression tube in Japanese studies and were found to be controversial. [18][19][20][21][22] Several studies that focused on the clinical safety and effectiveness of the self-expandable colonic stent have been conducted in the last 3 years in Japan, most of which were limited to advanced colon cancer patients who were bridged before surgical curative therapy. [1][2][3][5][6][7][8][9][10][11] The present study aimed to compare the utility (technical and clinical success rates) and the safety (rate of early and late complications after stent placement) of the colonic stent between patients who received systemic chemotherapy or palliative treatment and the best supportive care and patients who were bridged for surgery.…”
Section: Introductionmentioning
confidence: 99%